2018
DOI: 10.1002/slct.201702706
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom‐Doped Carbon Nanomaterials as Metal‐Free Catalysts for the Reduction of 4‐Nitrophenol

Abstract: In this work it is described the preparation and characterization of multi-walled carbon nanotubes and graphene flakes doped with heteroatoms, namely N, P, B, and S, through simple ball milling procedures with adequate precursors, followed by thermal treatments. Ball milling the carbon nanomaterials with melamine resulted in the introduction of pyrrolic, pyridinic and quaternary N atoms on the graphitic structure. Using triphenylphosphine as the phosphorous precursor induced the formation of RÀO-PO(OH) 2 funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Estimations show that a quarter of all chemical processes include at least one catalytic hydrogenation step [6]. Hydrogenation of nitrophenol (NP) to aminophenol is a typical reaction important for both environmental remediation and chemical stock production, considering that nitrophenols are hard-to-degrade compounds and exist widely in industrial wastewater [7]. The aminophenols are important intermediate products for synthesizing fine chemicals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Estimations show that a quarter of all chemical processes include at least one catalytic hydrogenation step [6]. Hydrogenation of nitrophenol (NP) to aminophenol is a typical reaction important for both environmental remediation and chemical stock production, considering that nitrophenols are hard-to-degrade compounds and exist widely in industrial wastewater [7]. The aminophenols are important intermediate products for synthesizing fine chemicals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the MoS 2 nanomaterials is catalytically active for the reduction of 4‐NP to 4‐AP . However, most of the reported MoS 2 nanomaterials are ultrathin nanosheets, which are difficult to recycle from solution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the MoS 2 nanomaterials is catalytically active for the reduction of 4-NP to 4-AP. [27][28][29][30] However, most of the reported MoS 2 nanomaterials are ultrathin nanosheets, which are difficult to recycle from solution. Moreover, the catalytic activity is mainly from the edge sites rather than the basal sites, which result in lower catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[101] Alternatively, hydrogen addition is used in mechanochemical reduction of graphene oxide. [102] Meanwhile an extraordinarily wide range of MFG bearing hydroxyl, carboxylic acid, halogen, five-,and six-membered N-heterocycles, sulfonic acid, and even phosphate groups have been prepared via graphite mechanochemistry in the presence of gases like CO 2 , [96,99] N 2 , [103,104] NH 3 , [105] H 2 , [106] O 2 , [100] Cl 2 , [107] F 2 , [107] and SO 2 , [99] liquids like Br 2 , [106,107] H 2 O, [108] SO 3 , [99,109] CO 2 /SO 3 , [99] as well as solids like red phosphorous, [110,111] sulfur, [112][113][114][115] melamine, [116][117][118][119] urea, [104,120,121] KOH, [122] NaCl, [123] Mg, [101] Fe, [124] Si, [125][126][127] polystyrene, [128] cellulose, [64] chitin, [129] polyvinylpyrrolidone, [130] polyetherketone, [131] and I 2 . [106,…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile an extraordinarily wide range of MFG bearing hydroxyl, carboxylic acid, halogen, five‐ ,and six‐membered N ‐heterocycles, sulfonic acid, and even phosphate groups have been prepared via graphite mechanochemistry in the presence of gases like CO 2 , N 2 , NH 3 , H 2 , O 2 , Cl 2 , F 2 , and SO 2 , liquids like Br 2 , H 2 O, SO 3 , CO 2 /SO 3 , as well as solids like red phosphorous, sulfur, melamine, urea, KOH, NaCl, Mg, Fe, Si, polystyrene, cellulose, chitin, polyvinylpyrrolidone, polyetherketone, and I 2 . The applications of MFGs spans from catalysts to energy material systems and polymer nanocomposites .…”
Section: Introductionmentioning
confidence: 99%